2012
DOI: 10.1002/hbm.22198
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity abnormalities extend beyond the sensorimotor network in peripheral neuropathy

Abstract: In PN, RS FC modifications extend beyond the sensorimotor network and involve other sensory and cognitive networks. The correlations between RS FC patterns and disease duration in patients as well as with clinical impairment in patients with APN suggest that modifications of FC might reflect an adaptive mechanism, which takes time to occur and helps to limit the clinical consequences of peripheral damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Enhanced interconnection of bilateral insula especially in HNP patients may reflect a similar mechanism in these sensory limbic structures trying to maintain selfawareness and homeostasis (15). This is in accordance with a previous study reporting that patients with peripheral neuropathy, both hereditary and acquired, exhibited multiple resting state functional connectivity abnormalities involving the sensorimotor, auditory and visual networks in comparison to healthy controls (16). Analogous to our results, the authors demonstrated increased resting state bold signal in posterior cingulate cortex/precuneus and suggested these modifications might reflect an adaptive mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced interconnection of bilateral insula especially in HNP patients may reflect a similar mechanism in these sensory limbic structures trying to maintain selfawareness and homeostasis (15). This is in accordance with a previous study reporting that patients with peripheral neuropathy, both hereditary and acquired, exhibited multiple resting state functional connectivity abnormalities involving the sensorimotor, auditory and visual networks in comparison to healthy controls (16). Analogous to our results, the authors demonstrated increased resting state bold signal in posterior cingulate cortex/precuneus and suggested these modifications might reflect an adaptive mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, functional connectivity (FC) analyses have provided invaluable approaches for studying the human brain in healthy ( Smith et al, 2009 , 2012 ; Yeo et al, 2011 ) and diseased groups ( Napadow et al, 2010 ; Collignon et al, 2013 ; Rocca et al, 2014 ) on the brain-network level. Among the varied functional neuroimaging techniques, resting-state fMRI (rs-fMRI) is a promising tool for mapping FC.…”
Section: Introductionmentioning
confidence: 99%
“…An increasingly popular approach to studying long-range interactions in both healthy ( Smith et al, 2009, 2012; Yeo et al, 2011 ) and clinical populations ( Collignon et al, 2013; Napadow et al, 2010; Rocca et al, 2014 ) is by measuring resting state functional connectivity. Functional connectivity is a measure of spatiotemporal synchrony of fMRI Blood-Oxygenation-Level-Dependent (BOLD) signal between anatomically distinct brain regions ( Friston et al, 1993 ), and it represents the degree of functional de/coupling between dissociated brain areas.…”
Section: Introductionmentioning
confidence: 99%